(3LhGgQ GdCOH aj COHjGJ hEfTGA dZI GdYQH (B/s - (3CMeO GdgGTej, CMeO Hf EHQGgje Hf eUWais 1878-1943 ((3HjQhJ (B:s (3OGQ GHf MRe,s, 2018)
(3gPG cJGH SejJg (B"(3LhGgQ GdCOH, aj COHjGJ dZI GdYQH(B" (3ChOYJg eG hbY Ydjg GNJjGQj, dG ef fKQj hGTYGQj, adjS dj aj JCdjag ef GdGaJNGQ CcKQ ef GdGNJjGQ, hGNJjGQ GdeQA bWYI ef Ybdg, JOd Ydi JNdbg haVdg, haVjdI gPG GdJCdja gj aj LeY eG GaJQb, eeG JfGSH hGJSb, hGNJjGQ Yjhf, hJQJjH afhf, ef CMGOjK fHhjI, hecGJHGJ COHjI hMce HGgQI, hCHjGJ fGOQI, hCeKGd TGQOI, hGNHGQ hCQOI, hhUGjG fGaYI hehGYX LGeYI, hefGXQGJ eSJXQaI, hebGeGJ eSJWQaI, hChUGa YdjI hNWH GLJeGYjI, hGddg SHMGfg hJYGdi gh Gdehab ddUhGH, Edjg GdeQLY hGdeBH(B.s
Keywords: (3GdCOH GdYQHjs -- (3JGQjN hfbOs; (3GdTYQ GdYQHjs -- (3JGQjN hfbOs; (3GdQSGFd GdYQHjIs -- (3JGQjN hfbOs